An estimate on the non‐real spectrum of a singular indefinite Sturm‐Liouville operator. Issue 1 (15th March 2018) - Behrndt, Jussi; Gsell, Bernhard; Schmitz, Philipp; Trunk, Carsten
Abstract: It will be shown with the help of the Birman‐Schwinger principle that the non‐real spectrum of the singular indefinite Sturm‐Liouville operator sgn(·)(−d 2 /d x 2 + q ) with a real potential q ∈ L 1 ∩ L 2 is contained in a circle around the origin with radius ‖ q ‖ L 1 2 . (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)